Evidence for Mallard Anas platyrhynchos and American Black Duck Anas rubripes 144 competition in western New Brunswick, Canada - Petrie, Mark J; Drobney, Ronald D; Sears, Dan T; Armstrong, Llewellyn M (Wildfowl, 2012)
The hypothesis that Mallard Anas platyrhynchos and American Black Duck Anas rubripes compete during the breeding period has generated considerable debate. To further evaluate this hypothesis, the following predictions were tested for sympatric Mallard and Black Duck breeding in New Brunswick: 1) Mallard and Black Duck do not partition breeding resources in space and/or time, 2) Mallard reduce the amount of breeding habitat available to Black Duck, and 3) production of Mallard and Black Duck is inversely related over time. Study results supported all predictions. Mallard and Black Duck pairs were distributed among wetland classes independent of species, though Black Duck were more likely to be observed alone or without Mallard on wetlands that were surrounded by > 75% upland forest. Mallard and Black Duck hatch dates did not differ, indicating they do not temporally partition breeding resources. Black Duck were more likely to be observed on wetlands where Mallard had been removed than on wetlands where they were not removed. This result supported the prediction that Mallard reduce the availability of breeding habitat for Black Duck through interference competition. To test the prediction that production of Mallard and Black Duck is inversely related over time, brood surveys were conducted from 1990 to 1994 to determine relative and absolute changes in numbers of Mallard and Black Duck broods. The ratio of Black Duck to Mallard broods declined from 0.938 in 1990 to 0.244 in 1994. Total number of Black Duck broods on 59 wetlands surveyed with equal effort in 1990 and 1994 declined from 45 in 1990 to 19 in 1994, while Mallard broods increased from 48 in 1990 to 78 in 1994. These findings support the hypothesis that Mallard and Black Duck compete.